English Teaching Material Development Based on Tynker Program in Improving Fourth-Grade Students’ Vocabularies - Haswani, Fahri; Nuran, Ade Aini (International Journal Labs, 2022)
In 21st-century learning, students must have access to communication, collaboration, critical thinking and problem solving, dan creativity, and innovation, including elementary students. Tynker is a platform for learning programming for kids that teaches them game design, web design, animation, and robotics. The study aimed to develop English teaching material based on the Tynker program to improve the vocabularies of fourth-grade elementary students. The subject of the study was 20 students in fourth grade in Zia Salsabila Private School. The researchers used Research and Development design in this study. The techniques of collecting data were observation, interview, and questionnaire. Furthermore, the researchers analyzed the data using descriptive qualitative and quantitative analysis. The result of the study showed that English teaching material based on the Tynker program improved students' motivation for vocabulary learning. Tynker-based teaching resources can be an alternate learning tool for fourth-grade elementary school pupils, particularly for developing vocabulary. The Tynker Program can help as a tool for learning English, but the researchers recommend using it with the proper learning resources. The teacher can download the Tynker program and develop their lesson plans using some of Tynker's topics. The teacher can use Tynker to give students resources for learning English and assist them in subjects where they feel learning English is difficult or dull.